2003
DOI: 10.1021/ja029024r
|View full text |Cite
|
Sign up to set email alerts
|

A Neutral Xenon-Containing Radical, HXeO

Abstract: We report an open-shell species containing xenon, HXeO ((2)Sigma), prepared by UV photolysis of H(2)O/Xe or N(2)O/HBr/Xe solid mixtures at 7 K and subsequent thermal mobilization of oxygen atoms at >/=30 K. The H-Xe stretching absorption of HXeO in solid Xe is at 1466.1 cm(-1), and it shifts to 1070.3 cm(-1) upon deuteration. The extensive ab initio calculations indicate that HXeO is intrinsically stable, owing to significant ionic and covalent contributions to its bonding. The formation of HXeO ((2)Sigma) rad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
48
1

Year Published

2003
2003
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 81 publications
(54 citation statements)
references
References 25 publications
5
48
1
Order By: Relevance
“…The appearance of formyl radical (peaks at 1863. 5 56 were observed in IR spectra after warming the samples to higher temperatures (26,33, and 45 K for Ar, Kr, and Xe matrices, respectively). The corresponding annealing dependencies are presented in Figure 5.…”
Section: Resultsmentioning
confidence: 86%
See 1 more Smart Citation
“…The appearance of formyl radical (peaks at 1863. 5 56 were observed in IR spectra after warming the samples to higher temperatures (26,33, and 45 K for Ar, Kr, and Xe matrices, respectively). The corresponding annealing dependencies are presented in Figure 5.…”
Section: Resultsmentioning
confidence: 86%
“…25 On the other hand, it was found that formation of the HXeO radical was determined by reactions of mobile oxygen atoms in xenon. 26,27 Thus, the IR spectroscopic studies of formation of different xenon hydrides allow one to follow the dynamics and reactivity of both hydrogen and oxygen atoms.…”
Section: Introductionmentioning
confidence: 99%
“…3, the first scheme (a two-stage dissociation of H 2 O) works quite well: the IR spectrum obtained after annealing of H 2 O/Xe sample irradiated with fast electrons to high dose reveals a well-defined band of the HXeO . radical (maximum at 1466 cm -1 [62]). In the case of N 2 O, one needs an additional source of H atoms.…”
Section: Production Of Oxygen Atoms and Ionsmentioning
confidence: 99%
“…We have used several different hydrogenated molecules for this purpose. The common procedure was similar to that used in photochemical studies [62]: irradiation of the system HY/N 2 O/Xe at low temperature following by annealing at 35 K to mobilize selectively trapped O atoms. However, in contrast to photolysis, the radiation-chemical experiments yield virtually no HXeO .…”
Section: Production Of Oxygen Atoms and Ionsmentioning
confidence: 99%
“…5(e),(f)). 52 Obviously, eqn (12)-(17) might be infinitely modified and extended to derivatives of C, N, S, Cl etc. Notably, studies of the thermal stability of the reaction products (on warming of the matrix) would show how realistic is the prospect of obtaining these and related species in larger quantities 'in the flask'.…”
Section: Still More New Bonds As It Gets Coldermentioning
confidence: 99%